They all fall down - Hall, Rachel Howzell (Forge, 2019)
"It was supposed to be the trip of a lifetime. Delighted by a surprise invitation, Miriam Macy sails off to a luxurious private island off the coast of Mexico, with six strangers--an ex-cop, a chef, a financial advisor, a nurse, a lawyer, a young widow. Surrounded by miles of open water in the gloriously green Sea of Cortez, Miriam is shocked to discover that she and the rest of her companions have been brought to the remote island under false pretenses--and all seven strangers harbor a secret. Danger lurks in the lush forest and in the halls and bedrooms of the lonely mansion. Sporadic cell-phone coverage and miles of ocean keeps the group trapped in paradise. And strange accidents keep them suspicious of each other, as one by one . . . They all fall down. For fans of thrilling contemporary suspense like The Woman in Cabin 10, Rachel Howzell Hall's brilliant stand-alone novel modernizes and pays homage to Agatha's Christie's And Then There Were None, bringing a diverse cast of seven sinners to a private island for a reckoning that will leave you breathless"--